The Effect of Organizational Justice and Workload on Turnover Intention with Job Stress as a Mediating Variable - Haryo Bhaskoro; Noermijati Noermijati; Nanang Suryadi (Politeknik Siber Cerdika Internasional, 2024)
This study was conducted to examine the relationship of organizational justice to turnover intention and the relationship of workload to turnover intention using 221 employees of PT. Telkom Access Indonesia, Tbk Malang City as the subject of research. Researchers examined the direct effect of organizational justice and workload on turnover intention. Researchers use job stress as a mediator of organizational justice and workload relationships to turnover intention. This study used the Warp PLS 8.0 application to test the relationship between variables. The results of this study found that organizational justice had a significant effect on turnover intention, while workload in the study did not have a significant effect on turnover intention. Furthermore, job stress mediates the relationship of organizational justice to partial turnover intention and mediates the relationship of workload to full turnover intention.